2014
DOI: 10.1371/journal.pone.0094834
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heart-Type Fatty Acid-Binding Protein with Cardiovascular Risk Factors and All-Cause Mortality in the General Population: The Takahata Study

Abstract: BackgroundDespite many recent advances in medicine, preventing the development of cardiovascular diseases remains a challenge. Heart-type fatty acid-binding protein (H-FABP) is a marker of ongoing myocardial damage and has been reported to be a useful indicator for future cardiovascular events. However, it remains to be determined whether H-FABP can predict all-cause and cardiovascular deaths in the general population.Methods and ResultsThis longitudinal cohort study included 3,503 subjects who participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 46 publications
(55 reference statements)
2
35
0
Order By: Relevance
“…H-FABP is more specific for heart muscle than are other types of fatty acid binding protein 30,31 . H-FABP is undetectable in normal conditions but is released rapidly from cardiomyocytes into circulating blood after myocardial damage.…”
Section: Discussionmentioning
confidence: 97%
“…H-FABP is more specific for heart muscle than are other types of fatty acid binding protein 30,31 . H-FABP is undetectable in normal conditions but is released rapidly from cardiomyocytes into circulating blood after myocardial damage.…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, FABP3 might be a sensitive marker for various cardiovascular risks, beyond acute myocardial injury. Indeed, a large population study showed that higher serum levels of FABP3 are associated with a great number of cardiovascular risks, suggesting that it could predict overall cardiovascular mortality within a general population (Otaki et al, 2014). However, cTnI seems to be a more sensitive biomarker for myocardial damage based on our functional, biomarker and transcriptional data, and therefore, a combined assessment of cTnI and FABP3 could be a valuable surrogate to evaluate chronic cardiotoxicity in hiPS-CMs.…”
Section: Figurementioning
confidence: 95%
“…H-FABP levels were measured using a two-step sandwich enzyme-linked immunosorbent assay (ELISA) kit (MARKIT-M H-FABP, Dainippon Pharmaceutical Co. Ltd., Tokyo, Japan), as previously described [15, 16]. …”
Section: Methodsmentioning
confidence: 99%